Application of Strain Criminology Theory in Analysing The Motives and Driving Factors of Perpetrators of Administrative Document Forgery - Yulia Christy Shintara Aruan; Suci Ramadani; Rahmayanti Rahmayanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The criminal act of falsifying administrative documents related to civil registration is a form of crime that has serious implications for the order of state administration, public trust, and the validity of civil registration data. This study aims to analyse the motives and driving factors of perpetrators in falsifying administrative documents related to civil registration through the application of strain criminology theory. The research method used is normative legal research with a criminological approach, supported by a literature study of relevant laws, regulations, doctrines, literature, and court decisions. The results show that the falsification of administrative documents is influenced by the gap between the cultural goals of society—such as obtaining employment, education, and social status—and the limitations of available legal means. Social pressure, economic conditions, and negative experiences such as frustration and bureaucratic obstacles encourage individuals to commit illegal acts as a form of adaptation. In addition, other contributing factors include weak social control, opportunities created by an ineffective administrative system, and the influence of a permissive social environment on forgery practices. The conclusion of this study confirms that the crime of falsifying administrative documents is not solely an individual problem, but also a structural and systemic one. Therefore, prevention efforts must be comprehensive, not only through strict law enforcement, but also by improving the administrative system, strengthening bureaucratic oversight, and reducing the socio-economic pressures faced by the community.